The effect of a braking device in reducing the ground impact forces inherent in plyometric training - Humphries, B. J.; Newton, R. U.; Wilson, G. J. (International Journal of Sports Medicine, 1995)
As a consequence of performing plyometric type exercises, such as depth jumps, impact forces placed on the musculoskeletal system during landing can lead to a potential for injury. A reduction of impact forces upon landing could therefore contribute to reduce the risk of injury. Twenty subjects performed a series of loaded jumps for maximal height, with and without a brake mechanism designed to reduce impact force during landing. The braked jumps were performed on the Plyometric Power System (PPS) with its braking mechanism set at 75% of body weight during the downward phase. The non-braked condition involved jumps with no braking. Vertical ground reaction force data, sampled for 5.5 s at 550 Hz from a Kistler forceplate, were collected for each jump condition. The following parameters were then calculated: peak vertical force, time to peak force, passive impact impulse and maximum concentric force. The brake served to significantly (p < 0.01) reduce peak impact force by 155% and passive impact impulse by 200%. No significant differences were found for peak concentric force production. The braking mechanism of the PPS significantly reduced ground impact forces without impeding concentric force production. The reduction in eccentric loading, using the braking mechanism, may reduce the incidence of injury associated with landings from high intensity plyometric exercises.